Analysis of Internal and External Environmental Influenceson Organizational Effectiveness - Chiesa Syahwanes, Adnin; Saepudin, Eli Apud; Azzahra, Shabna; Karmila , Diah; Zulzana, Tika; Solehatunnisa, Firlyn (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Organizations operate in an environment that is dynamic, complex, and full of change. An organization’s success in achieving its goals depends on its ability to adapt and respond to these changes. This research aims to analyze the influence of the internal and external environment on organizational effectiveness. Data was collected from 100 organizations in Indonesia through surveys. The internal environment has a positive and significant influence on organizational effectiveness, the external environment has a positive and significant influence on organizational effectiveness, the organizational environment can be divided into the internal environment and the external environment, the internal environment is related to the strengths and weaknesses of the company, the external environment is the general environment as well as the industrial environment outside the company’s internal environment which is an opportunity or obstacle for the company. The relationship between the business environment and the organization or company, namely the external environment as a source for suppliers of resources and consumers of output. How much this environment can support the organization can have an impact on the organization’s operations and performance. The internal environment has a direct influence on the level of capability in the process which includes the three subsystems in the organizational system, namely input, transformation and output. this research is that organizational effectiveness is influenced by internal and external factors, as well as the interaction between these two factors. It is hoped that the results of this research will provide benefits for organizational leaders in understanding the factors that influence organizational effectiveness, as well as in formulating appropriate strategies and policies toincrease organizational effectiveness.